Strengthening Policy Communication For Sustainable Development of Islamic Practices In Singkawang City - Syarifah Aminah; Fitri Kusumayanti; Suhaimi Suhaimi; Noviansyah Noviansyah (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
The development of the religious sector stands as a crucial component within the national development agenda. The government’s endeavors aim to harmonize development programs within this sector, fostering societal independence amid diversity. This research seeks to formulate alternative policy models for ensuring sustainable Islamic development. Adopting a systems thinking approach with dynamic systems methods. The method used is a dynamic system model, which includes the dimensions of the Muslim population submodel, the santri submodel, and the muallaf population submodel. The study deliberately selected Singkawang City as its research location through purposive sampling. Simulations conducted span the period from 2023 to 2033, revealing scenarios within the Muslim community sub-model. The Muslim population sub-model built in the dynamic system is a population dynamics system or human resources in the Muslim community of Singkawang City. Islamic boarding school students sub-model at religious educational institutions and the Muslim convert population sub-model. The muallaf population submodel is the number of muallaf people in Singkawang City. Policy alternatives emerge as priorities for simulations and scenarios in achieving sustainable development of Islamic practices. The analysis of alternative scenarios emphasizes the necessity for support of religious development policies by both the Singkawang City government and the central government. The rise in the Muslim resident population requires proactive measures, such as increasing the number of Islamic religious instructors and strengthening social and religious institutions dedicated to religious programs. Furthermore, efforts in Islamic religious education are crucial for enhancing human resources. Improved religious programs tailored to the Muslim populace, including religious guidance and convert-based empowerment initiatives, serve as integral components of sustainable Islamic development.